Mechanisms of Yajieshaba in the treatment of liver fibrosis through the Keap1-Nrf2 signaling pathway - Bai, Yuanmei; Wu, Haimei; Zheng, Lijie; Xie, Yuhuan; Liu, Feifan; Wan, Yan; Li, Qiongchao; Guo, Peixin (Frontiers in Pharmacology, 2023)
Yajieshaba (YJSB), a traditional Dai medicine formula containing botanical drugs, is commonly employed in Yunnan due to its significant therapeutic effects on liver protection. Consequently, to determine the efficacy of YJSB and the mechanism of action of Kelch-like ECH-associated protein 1 (Keap1)-nuclear factor erythroid 2-related factor 2 (Nrf2) pathway against liver fibrosis. We wanted to see if YJSB could treat CCl4-induced liver fibrosis by regulating the Keap1-Nrf2 signaling pathway. YJSB significantly improved liver function biochemical indices, liver fibrosis quadruple, hydroxyproline (Hyp), and transforming growth factor-β1 (TGF-β1) levels. The staining results demonstrated that the degree of liver fibrosis was significantly reduced. YJSB reduced the content of malondialdehyde (MDA) and elevated the content of superoxide dismutase (SOD) in the liver, exhibiting antioxidant effects; meanwhile, it regulated the expression of Keap1-Nrf2 pathway protein, increased the expression of NAD(P)H: Quinone oxidoreductase (NQO1), Heme Oxygenase 1 (HO-1), Glutamate cysteine ligase modifier subunit (GCLM), and Glutamate cysteine ligase catalytic subunit (GCLC) expression in the liver decreased while Nrf2 expression increased. Fluorescence immunoassay studies demonstrated that YJSB promoted the trans-nuclearization of Nrf2. YJSB possesses anti-liver fibrosis pharmacological effects that improve liver function and effectively counteract CCl4-induced liver fibrosis damage. The mechanism of action might be related to the regulation of protein expression of the Keap1-Nrf2 pathway, increasing the ability of the body to resist oxidative stress and reduce oxidative stress injury.